Pengaruh Shariah Governance, Capital Adequacy Ratio (CAR), dan Financing to Deposit Ratio (FDR) Terhadap Pengungkapan Islamic Social Reporting - Lala Handayani; Harti Budi Yanti (Publikasi Indonesia, 2023)
The purpose of this study is to know the impact of these factors on Islamic Social Repoting disclosure in the islamic banks consisting of Islamic Commercial Banking and Islamic Banking Syariah in Indonesia listed in Otoritas Jasa Keuangan. This study uses secondary data obtained from Islamic banks’s annual report from the period 2016 to 2020. The sampling method used in this study was purposive sampling technique. The analysis technical in this study used panel data regression analysis method using eviews program. Based on the result of the T test, it shows that frequency of sharia supervisory board meeting has a significant effect on islamic social reporting disclosure. Meanwhile, the size of sharia supervisory board, the sharia supervisory board expertise, capital adequacy ratio, and financing to deposit ratio have no significant effect on islamic social repoting disclosure.